Nanoporous Carbon from Durian Peel via Hydrothermal-Carbonization and their Application in Ripening Delay of Durian - Thanat Sitthisantikul; Pee Poolsili; Jindabha Devakula; Anuchit Jaruwanawat; Apiluck Eiad-Ua (My University, 2020)
Abstract This research was aimed to examine conditions on synthesis of nanoporous carbon materials from durian peel via the process of hydrothermal carbonization (HTC) as an application for delaying durian ripening process. The experiment was conducted by using durian peel as materials for producing nanoporous carbon via the process of hydrothermal at 160-200 °C for 8-24 hours. It also included the process of carbonization at 500-900 °C for 2 hours under nitrogen atmosphere for developing pore structure and removing contaminants to obtain the nanoporous carbon. The properties of nanoporous carbon were characterized by scanning electron microscope (SEM), Fourier transform infrared spectroscopy (FT-IR) and Raman spectrometer analysis. The results indicated that the process of hydrothermal at 200 °C for 12 hours and carbonization at 900 °C for 2 hours was suitable for delaying ripe durian. This is become of the carbon content, porous structure and amorphous structure increased with HTC temperature.
Keywords: Hydrothermal Carbonization; Nanoporous; Carbon fibers; null